Narrowband interference suppression in vector OFDM systems - ZHANG Guo-mei; ZHU Shi-hua (Tongxin xuebao)
The effect of narrowband interference on the performance of vector OFDM （VOFDM） was analyzed and a narrowband interference suppression method for VOFDM was proposed. By modifying the received vector sequences, the reception over vector channels in a VOFDM system was converted to the detection in a MC-CDMA system. Then the minimum mean-square error combining （MMSEC） technique was adopted to suppress the narrowband interference. Per- formance analysis and simulation results show that the proposed receive method can improve the system robustness to narrowband interference. When signal-interference-ratio （SIR） is 15dB and the target bit error rate is 10-2, the proposed method can obtain 8dB gain compared to the least square （LS） detection with the vector length being 16.